Analysis of Flow and Runner Dynamic Response Characteristics under Pump Conditions of Variable-Speed Pump Turbine - Linmin Shang; Jingwei Cao; Lei Wang; Shuang Yu; Sen Ding; Zichao Wei; Zhengwei Wang; Xiaobing Liu (Journal of Marine Science and Engineering, 2023)
Pumped storage power stations can ensure the safe operation of the grid, as well as utilize clean energy sources to establish a low-carbon, safe, and efficient energy system. As pump turbines, the core components of pumped storage power plants, become more and more popular, the technical requirements for hydraulic design begin to improve year by year. However, when the unit operates far beyond the optimal range, the variable-speed pump turbine can overcome the shortcomings of the fixed-speed unit and solve the problem of unstable operation under partial load. The pressure pulsation of the unit in the pump condition is investigated by numerical simulation, analyzing the hydraulic thrust, and studying the dynamic response characteristics of the runner at a maximum speed of 456.5 rpm. Comparing the pressure pulsation amplitude of various components in the entire flow passage, the highest values of pressure pulsation were found in the runner and vaneless space. The axial hydraulic thrust has a fluctuation range between 174t and 198t and 0t to 40t for radial force. As per the structural analysis, it has been observed that the runner demonstrates uneven patterns in both its axial and radial deformations, with deformation mainly concentrated in radial displacement and stress distribution mainly concentrated on the blades near the crown. The dynamic stress amplitude of the runner at monitoring point S1 (located on the runner blade near the crown) is 37 MPa. This stress has a dominant frequency of 4.8fn, while the monitoring point S2 (located on the runner blade near the band) is 4 MPa, and the dominant frequency is 1.8fn. Using these findings, the design of the variable-speed pump turbine’s runner can be optimized, and the unit’s stable and secure operation can be guided accordingly.